Stable Cu Isotope Ratios Show Changes in Cu Uptake and Transport Mechanisms in Vitis vinifera Due to High Cu Exposure - Blotevogel, Simon; Oliva, Priscia; Denaix, Laurence; Audry, Stéphane; Viers, Jerome; Schreck, Eva (Frontiers in Plant Science, 2022)
Even though Cu is an essential plant nutrient, it can become toxic under certain conditions. Toxic effects do not only depend on soil Cu content, but also on environmental and physiological factors, that are not well understood. The mechanisms of Cu bioavailability and homeostasis of vitis vinifera were investigated in this study under controlled conditions, using stable Cu isotope analysis. We measured Cu contents and δ65Cu isotope ratios in soils, soil solutions, roots and leaves of grapevine plants grown on six different vineyard soils, in a 16-week greenhouse experiment. The mobility of Cu in the soil solutions was controlled by the solubility of soil organic matter. No direct relationship between Cu contents in soils or soil solutions and Cu contents in roots could be established, indicating a partly homeostatic control. Isotope fractionation between soil solutions and roots shifted from light to heavy with increasing Cu exposure, in line with a shift from active to passive uptake. Passive uptake appears to exceed active uptake for soil solution concentrations higher than 270 µg L-1. Isotope fractionation between roots and leaves was increasingly negative with increasing root Cu contents, even though leaf Cu contents did not differ significantly. Our results suggest that Cu isotope analysis is a sensitive tool to monitor differences in Cu uptake and translocation pathways even before differences in tissue contents can be observed.